PASHTUN IMAGES IN CONTEMPORARY PAKISTANI FICTION IN ENGLISH - Syed Hanif Rasool (University of Chitral Journal of Linguistics and Literature, 2025)
Living in an area that has long been a battlefield where various world powers have often been at loggerheads, Pashtuns have frequently drawn the attention of several works of fiction. Yet literary scholars have largely ignored the importance of these works of fiction looking into the lives of Pashtuns. This paper proposes that from the times of the Cold War to those of the War on Terror, Pashtun identities have been clouded by the hegemonic discourses of the contesting global powers, leading to gaps and silences in their depiction in literature.This paper argues that the Pashtun images in contemporary Pakistani fiction in English exhibit strong influences of the dominating narratives; simultaneously, however, they seem to offer various patterns of subversion of the prevailing power narratives. Despite the fact that Pashtuns are generally regarded as the most subversive people of South Asia and that their lands have been regarded significant strategically as well as geographically, yet they are portrayed as the Others of the mainstream cultural discourses. This paper aims to highlight the contours of the socio-cultural and political valuation of Pashtuns in contemporary Pakistani fiction in English.